Optimization of Salicylic Acid Dose to Improve Lettuce Growth, Physiology and Yield Under Salt Stress Conditions - Kiremit, Mehmet Sait (Springer Science and Business Media Deutschland GmbH, 2023)
In irrigated agriculture, soil salinity threatens the sustainability of crop productivity and global food security by reducing water quantity and quality. Therefore, foliar spraying with protectants has proven to be an efficient method for diminishing the effects of salt stress and boosting crop growth performance. The present study was conducted to explore the effects of different doses of salicylic acid (SA) on evapotranspiration (ET), yield, growth, and physiology of lettuce (Lactuca sativa L.) under saline irrigation conditions. Additionally, response surface methodology was employed to identify the most effective dose of SA for lettuce plants under saline irrigation conditions. At the lowest salinity (0.30 dS m−1), 1.0 mM and 2.0 mM SA foliar applications increased yield by 29.7% and 6.8%, respectively, compared with 0 mM SA. At the same salinity, chlorophyll content and stomata increased by 35.6% and 22.6%, respectively, at 1.0 mM SA and 10.4% and 8.2%, respectively, at 2.0 mM SA compared to the 0 mM SA dose condition. Moreover, ET was reduced by 56.4%, 50.1%, and 55.5% at 0, 1, and 2 mM SA doses, respectively, when water salinity increased from 0.30 to 8.0 dS m−1. The optimal SA dose and irrigation water salinity were identified as 0.88 mM and 0.32 dS m−1, respectively. In conclusion, this study provides important guidelines for the effective use of SA in lettuce production under salt-stress conditions, with implications for improving the quantitative and qualitative traits of lettuce irrigated with saline water in regions of freshwater scarcity. © 2023, The Author(s), under exclusive licence to Springer-Verlag GmbH Deutschland, part of Springer Nature.
Keywords: Desirability Analysis; Lactuca Sativa L; Modeling; Response Surface Methodology; Salinity